Gender gaps in cognitive and social‐emotional skills in early primary grades: Evidence from rural Indonesia. Issue 5 (8th January 2020) - Nakajima, Nozomi; Jung, Haeil; Pradhan, Menno; Hasan, Amer; Kinnell, Angela; Brinkman, Sally
Abstract: This paper examines the magnitude and source of gender gaps in cognitive and social‐emotional skills in early primary grades in rural Indonesia. Relative to boys, girls score more than 0.17 SD higher in tests of language and mathematics (cognitive skills) and between 0.18 and 0.27 SD higher in measures of social competence and emotional maturity (social‐emotional skills). We use Oaxaca–Blinder decomposition to investigate the extent to which gender differences in early schooling and parenting practices explain these gender gaps in skills. For cognitive skills, differences in early schooling between boys and girls explain between 9% and 11% of the gender gap whereas differences in parenting practices explain merely 3%–5% of the gender gap. This decomposition result is driven largely by children living in villages with high‐quality preschools. In contrast, for social‐emotional skills, differences in parenting styles toward boys and girls explain between 13% and 17% of the gender gap, while differences in early schooling explain only 0%–6% of the gender gap. Abstract : A selection of results from Table 4 are shown. Line shows magnitude of gender gap. Point estimates are reported using black data labels. Each section of the bar shows the share of the gender gap explained. Shares are reported using white data labels. Hollow sections are statistically insignificant. A small statistically insignificant negative estimate for the share of the gap explained by months of preprimary school in the case of emotional maturity is not visible. Unpacking gender gaps in cognitive and socio‐emotional skills, this paper finds that differences in parenting styles and in early schooling play a key role in explaining gaps in achievement between boys and girls. However, relative to each other, parenting styles seem to explain more of the gap in socio‐emotional skills while schooling seems to explain more of the gap in cognitive skills.